Proton pump inhibitors induced fungal dysbiosis in patients with gastroesophageal reflux disease - Shi, Yichao; Li, Jianfeng; Cai, Shuntian; Zhao, Hong; Zhao, Huijun; Sun, Gang; Yang, Yunsheng (Frontiers in Cellular and Infection Microbiology, 2023)
Gut mycobiota inhabits human gastrointestinal lumen and plays a role in human health and disease.We investigated the influence of PPIs on gastric mucosal and fecal mycobiota in patients with gastroesophageal reflux diseases (GERD) by using Internal Transcribed Spacer1 sequencing. A total of 65 participants were included consisting of health controls group (HC), GERD patients who did not use PPIs (nt-GERD), and GERD patients who used PPIs, which were further divided into short-term PPIs and mycobiota in GERD 2 (s-PPI) and long-term PPI user (l-PPI) group based on the duration of PPI use. The alpha diversity and beta diversity of gastric mucosal mycobiota in GERD patients with PPIs use were significantly different from HCs, but there were no differences between s-PPI and l-PPI groups.LEfSe analysis identified Candida at the genus level as a biomarker for s-PPI group when compared to the nt-GERD group. Meanwhile, Candida, Nothojafnea, Rhizodermea, Ambispora, Saccharicola, etc. were more abundant in l-PPI group than nt-GERD group. Furthermore, colonization of Candida in gastric mucosa was significantly increased after PPIs treatment. However, there was no significant difference in Candida colonization between patients with endoscopic esophageal mucosal breaks and those without.There were significant differences in the fecal mycobiota composition between HCs and GERD patients regardless whether or not PPI use. As compared to nt-GERD patient samples, there was high abundance of Alternaria, Aspergillus, Mycenella, Exserohilum, Clitopilus, etc. in s-PPI group. In addition, there was a significantly higher abundance of Alternaria, Aspergillus, Podospora, Phallus, Monographella, etc. in l-PPI group than nt-GERD patient.In conclusion, our study indicates that dysbiosis of mycobiota was presented in GERD patients both in gastric mucosal and fecal mycobiota. PPIs treatment may increase the colonization of Candida in the gastric mucosa in GERD patients.